Governance through Digital Platforms: A Study of the Effectiveness of e-Participation on Policy Transparency in the Philippines - Josephine Tan; Christopher Lum (Asian Digital Governance Problems, 2025)
Purpose: This study investigates the effectiveness of e-participation in enhancing policy transparency in the Philippines. As digital platforms are increasingly used for public engagement in policy-making, the study seeks to evaluate how these platforms influence government transparency and citizen participation. Subjects and Methods: The study employed a quantitative cross-sectional survey design involving 320 respondents consisting of citizens, government officials, and civil society representatives who had experience using digital governance platforms. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation analysis, and multiple linear regression with SPSS version 27. Results: The findings indicate that respondents generally perceived e-participation platforms positively, particularly regarding accessibility and digital literacy. Correlation analysis revealed a strong positive relationship between e-participation effectiveness and policy transparency. Regression analysis further demonstrated that institutional responsiveness was the strongest predictor of transparency outcomes. The results suggest that transparent digital governance depends not only on technological accessibility but also on responsive governmental institutions. Conclusions: E-participation significantly strengthens policy transparency and democratic engagement in the Philippines when supported by inclusive digital infrastructure and responsive governance practices.